Klatskin's tumor. Presentation of a patient - Luis Alberto Ibáñez Bravo; Julio C. López Soler; Jesús Isaac de Armas Prado (Acta Médica del Centro, 2007)
Klatskin's tumor usually presents as a diffuse nodular lesion, being refered to as colangiocarcinoma. It originates at the confluence of both hepatic ducts. This fact imposes the need of peering at hepatic ducts proximally in colangiography. First clinical manifestations of the disease includes biliar obstruction, thus producing a formerly painless jaundice, which later could become profound, in right hypochondrius, being fever rarely found. Because obstruction establishes gradually, diagnosis is often made at late stages when colangiocarcinoma produces clinical manifestations. Radiologically, biliar pathways enlarging is found. Radiotherapy and/or chemotherapy, together with external biliar pathway drainage improve clinical conditions palliatively.